2022
DOI: 10.1038/s41598-022-25207-0
|View full text |Cite
|
Sign up to set email alerts
|

Sap flow of sweet cherry reveals distinct effects of humidity and wind under rain covered and netted protected cropping systems

Abstract: Protected cropping systems (PCS) alter the plant growing environment, though understanding of this in ventilated systems and how the new climate affects tree water uptake is limited. Sap flow sensors and weather stations were deployed in 16-year-old ‘Lapins’ on ‘Colt’ rootstock cherry trees under a ventilated Voen PCS and in an adjacent bird netted PCS. Average and maximum temperatures were consistently higher (14.7 °C and 22.9 °C) while total daily solar radiation and average wind were consistently lower (12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Sap flow technology has been widely applied for the estimation of tree transpiration, analysis of soil water content level, management of water resources and analysis of tree health status. The main external factors affecting the sap flow rate of trees are environmental factors, such as saturated vapor pressure deficit [28], air relative humidity [69], air temperature [70], wind speed [26], soil moisture content [65], and soil temperature [71]. In this paper, an improved sap flow prediction model was built with environmental factors by factor analysis and the CNN-GRU-BiLSTM network we designed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sap flow technology has been widely applied for the estimation of tree transpiration, analysis of soil water content level, management of water resources and analysis of tree health status. The main external factors affecting the sap flow rate of trees are environmental factors, such as saturated vapor pressure deficit [28], air relative humidity [69], air temperature [70], wind speed [26], soil moisture content [65], and soil temperature [71]. In this paper, an improved sap flow prediction model was built with environmental factors by factor analysis and the CNN-GRU-BiLSTM network we designed.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that sap flow is significantly related to environment factors. Stone et al used the method of generalized additive modelling to predict the influence of individual climate parameters on sap flow, and the results show a 60% relative humidity (RH) critical threshold of predicted sap flow and the indirect effect that wind speeds have on sap flow under protected cropping systems [26]. Su et al used principal component analysis (PCA) to understand the response of sap flow to water stress and microclimatic variables, and the results showed that there was a positive correlation between vapor pressure deficit and daytime sap flow [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation